No Action Today, No Cure Tomorrow - A Review of Agricultural Factors Predisposing Humans at The Risk of Antimicrobial Resistance and Its Preventive Strategies - Akhtar Ali; Nimra Khalid; Syed Hasan Danish; Syed Wajid Shah (ziauddin University, 2024)
One of the most significant public health issues today is AMR (AMR), which poses significant difficulties in controlling and treating infectious diseases. It is believed that the abuse and overuse of numerous antibacterial agents in the healthcare and agriculture industries led to the emergence of antimicrobial resistance. Even though irrational prescriptions have been blamed for the rise in resistance among microbes to various antimicrobial drugs, a variety of environmental factors have also been linked to the development of multidrug-resistant (MDR) organisms. Several studies have stressed the significance of using a one-health approach, or a holistic strategy, to combat antibiotic resistance that takes into account people, animals, and the environment. Models describing how resistance starts and spreads could be created with a better understanding of the environmental factors that encourage its development. Yet, preventing the establishment and spread of mobile resistance elements is challenging since it is unclear how and when the environment favors resistance growth. Hence the current review focuses on the agricultural factors predisposing humans to the risk of AMR and preventive strategies.